MyBookStore-eshopping for books - Chitturi, Sushma Reddy (Kansas State University, 2010)
The Web is a shopper's paradise boasting every kind of product imaginable — plus many more that are almost unimaginable. People find it easy and secure to shop online these days thereby saving time and also have more options to choose from at their fingertips. Based on this comes MyBookStore, a neat web application designed to exclusively cater the needs of students for purchasing books online. Primary focus of this application is to ease the use of searching for a particular book by the user and also navigability within the website. A sophisticated search engine has been designed in this application which filters the products based on various user criterions. Searching and viewing the details about a book is available. This also has an administrator side through which the administrator can update the website with new products, remove any of the available products, and add new categories, subcategories and products along with updating the shipping status of orders placed. This section is majorly responsible for user accounts maintenance, product maintenance as well as orders maintenance. Major emphasis of this application is to build user interactive search techniques for simplifying user needs and to provide specific products as required by the user.
Keywords: Shopping Cart; Asp.Net; Ajax 3.0; E-Shopping; Computer Science (0984)